Assessment of the morphological profile of young swimmers using bioimpedance analysis of body composition - Inake, E.K. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to determine the characteristics of body composition and phase angle in young athletes prior to commencing regular swimming training. Methods and structure of the study. A bioimpedance analysis of the body composition of young athletes aged 7 (a total of 67 participants, comprising 25 girls and 42 boys) with no prior experience of regular swimming training was conducted. The ABC-01 ‘Medass’ device was used to assess body fat mass, body fat percentage, skeletal muscle mass and skeletal muscle percentage, active cellular mass, phase angle and body type. Results and conclusions. It has been established that in young athletes who are beginning to swim regularly, the key body composition parameters fall within the age-appropriate range. However, boys tend to have a higher proportion of lean body mass and a higher level of active cellular mass, whilst girls have a higher percentage of adipose tissue. Phase angle indices in both groups correspond to low values, reflecting the functional immaturity of cell membranes in children of this age. A predominance of the ectomeso-morphic body type was identified, indicating harmonious physical development and favourable conditions for young athletes to master swimming movements.